Event-based secure H∞ load frequency control for delayed power systems subject to deception attacks - Wang, Dongji; Chen, Fei; Meng, Bo; Hu, Xingliu; Wang, Jing (Applied mathematics and computation, 2021)
•An event -triggered scheme, whose objective is to reduce the pressure of data transmission caused by the limited network bandwidth resources, is employed in this paper.•Considering the impact of deception attacks, a new model for LFC power systems with time delays is established.•By adopting a novelty decoupling method, the desired controller gains can be obtained. This paper focuses on designing an H∞ load-frequency controller for power systems suffering from deception attacks based on the event-based secure control scheme. Firstly, to alleviate the occurrence of congestion phenomenon in the bandwidth-limited communication network, an event-triggered scheme is introduced into the sensor-to-controller channel. Subsequently, a mathematical model with regard to the event-triggered load frequency control is established under considering the existence of deception attacks. Then, in terms of Lyapunov stability theory and an improved inequality technique, some sufficient conditions that can ensure the mean-square asymptotic stability with a prescribed H∞ performance index of the closed-loop system are deduced. Besides, the corresponding controller gain is obtained by solving those conditions. Finally, two numerical examples are presented to verify the effectiveness of the proposed method.